2016
DOI: 10.1039/c6ra00150e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in 1,10-phenanthroline ligands for chemosensing of cations and anions

Abstract: This review encompasses and highlights recent developments of 1,10-phenanthroline ligands behaving as a customized moiety used in recognition and sensing of cations and anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 238 publications
0
50
0
Order By: Relevance
“…These complexes may bind various biomolecules and are used as enzyme inhibitors, biomarkers and biosensors . Synthetic chemistry of 1,10‐phenanthrolines is rich and provides various routes to fluorescent chemosensors and chemodosimeters . Varying structural featured of the ligands and the complexes, such as the nature, the number and position of substituents in the phenanthroline ring, the number of the phenanthroline ligands at metal centers, the selectivity and sensitivity of sensing can be finely tuned ,…”
Section: Amination Of Halogenophenanthrolines Phen With Aminementioning
confidence: 99%
“…These complexes may bind various biomolecules and are used as enzyme inhibitors, biomarkers and biosensors . Synthetic chemistry of 1,10‐phenanthrolines is rich and provides various routes to fluorescent chemosensors and chemodosimeters . Varying structural featured of the ligands and the complexes, such as the nature, the number and position of substituents in the phenanthroline ring, the number of the phenanthroline ligands at metal centers, the selectivity and sensitivity of sensing can be finely tuned ,…”
Section: Amination Of Halogenophenanthrolines Phen With Aminementioning
confidence: 99%
“…Compared to the bipyridine systems, the vast potential of disubstituted‐[1‐10]‐phenanthroline derivatives as NLO materials remains largely unexplored . The phenanthroline unit is one of the most common ligands in supramolecular photochemistry: it possesses an extended π system and shows relative inertness towards chemical reactions, other than salt formation and chelation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the bipyridine systems, the vast potential of disubstituted-[1-10]-phenanthroline derivatives as NLO materials remains largely unexplored. [29][30][31] The phenanthroline unit is one of the most common ligands in supramolecular photochemistry: it possesses an extended p system and shows relative inertness towards chemical reactions, other than salt formation and chelation. Furthermore, it can act as an acceptor group due to the deficiency of electron density while the nitrogen atoms may act as a bidentate preorganized ligand to form five membered chelate rings with either a metal or hydrogen ion.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21b,21c,22] Yet the rewards of isolating a species with a long lived fluorescent unit such as [Ru(bipy) 3 ] 2+ adjacent to an enclosed three dimensional cavity offers significant opportunities for the selective recognition of small molecules. [24] It has been shown to be of interest in the selective detection of anions, [4b,19,21a] but this has not been replicated with the successful recognition of cations. Nabeshima et al have reported a cavity with a suitable extended cavity space with a degree of selectivity for divalent cations such as Ca 2+ and Mg 2+ , but the protonation of a central nitrogen resulted in some interesting and unexplained effects.…”
Section: Introductionmentioning
confidence: 99%